ENDEMISME SPESIES BIOTA PERAIRAN: STUDI KASUS PADA IKAN CAPUNGAN BANGGAI (Pterapogon kauderni) - Ucu Yanu Arbi (OSEANA, 2022)
A species becomes endemic if found only in one place and not found elsewhere. Physical, climatic, and biological factors can cause endemism through two commonly known mechanisms, namely "autochthonous" and "allochthonous". The Banggai cardinalfish (Pterapogon kauderni) was an endemic fish from the Banggai Islands waters, Central Sulawesi. Biologically, these fish cannot spread beyond their original habitat. This apogonid fish was endemic due to several main contributing factors. First, slow movement which causes limited habitat distribution. Second, have paternal mouthbrooder characters so that they do not have a larval phase. Third, shows an ontogenetic shift in terms of microhabitat selection. Fourth, has a subpopulation that a criteria of Evolutionarily Significant Unit. This review aims to provide a brief review of the endemism of marine organisms with a case study on the Banggai cardinalfish.